Telaprevir drug monitoring during antiviral therapy of hepatitis C graft infection after liver transplantation. (9th April 2014) - Farnik, Harald; Zimmermann, Tim; Herrmann, Eva; Bechstein, Wolf O.; Kronenberger, Bernd; Galle, Peter R.; Labocha, Sandra; Ferreiros, Nerea; Geisslinger, Gerd; Zeuzem, Stefan; Sarrazin, Christoph; Welker, Martin W.
Abstract Background & Aims Recurrence of hepatitis C virus (HCV) infection after orthotopical liver transplantation (OLT) is common and associated with reduced graft and patient survival. The protease inhibitor telaprevir may enhance virological response rates in patients after OLT in combination with pegylated interferon‐alfa and ribavirin. Pharmacokinetic studies have shown significant drug–drug interactions between telaprevir and immunosuppression (IS), but telaprevir pharmacokinetics in OLT patients with IS are unknown. Aim of the present study was to analyse telaprevir plasma concentrations in patients with HCV genotype 1 infection after OLT in comparison to patients without OLT and IS. Methods Five patients with HCV genotype 1 infection after OLT and 37 HCV genotype 1‐infected patients patients without prior OLT were treated with telaprevir 2250 mg daily, ribavirin 1000/1200 mg daily and pegylated interferon‐alfa‐2a 180 μg once weekly (triple therapy). Telaprevir plasma concentrations were analysed by liquid chromatography–electrospray‐ionization‐tandem mass spectrometry. HCV RNA was assessed by automatized reverse‐transcription polymerase chain‐reaction. Results Median (range) telaprevir plasma concentrations of TW 4, 8 and 12 were 3970 (1980–4430) ng/ml and 2520 (1870–8730) ng/ml in patients after OLT and ciclosporin‐ or tacrolimus‐based IS, respectively, as compared to 2790 (1870–3140) in non‐OLT patients (P = 0.3). In one patient with tacrolimus‐based IS, telaprevir dose had to be adjusted to achieve virological response. Telaprevir plasma concentrations were steady at treatment weeks 4, 8 and 12 in patients with and without IS. Conclusions Telaprevir drug monitoring may be necessary in patients with tacrolimus‐based IS in patients with HCV graft infection after OLT.